Dropping out of a TEFL program: A study on internal factors - Marín Marín, Clara Lucero; Castañeda Useche, Yasbeidy (2021)
The current qualitative study focuses on internal factors as a cause of the dropping out problem of an undergraduate program. The phenomenon of higher education students’ desertion has received considerable attention, since it is a serious problem in Colombia. We want to understand why in a Teaching English as a Foreign Language program (TEFL) over 25% of the admitted drop out of the program at some point. The inquiry centers on problems that could be solved through pedagogy reviewing literature on dropping out and bringing comparative data from two other TEFL programs in Bogotá, Colombia. According to Hummel, (2014), these factors play an important role when learning a second language: intelligence aptitude, attitudes, motivation, personality, learning style, cognitive style, and learning strategies. We plan to concentrate on attitudes, motivation, and language learning strategies (Castillo, 2014), these factors conform the first construct developed along this inquiry. On the other hand, this study examines the second construct based on the dropping out which is described as the major problem found according to an institutional report of desertion. The institutional report shows how the dropping out increases as much as students advance semester by semester being the half from the incoming students who achieve to graduate at the end of a TEFL program. In this study, the desertion is a term defined as an abandonment that can be explained by diverse categories such as socioeconomic, individual, institutional and academic variables (MEN, 2009). In addition to this, the Deputy Minister of Higher Education of Colombia showed in a desertion report that about 600.000 students who annually graduate from high school, 45% succeed in entering higher education and of these, about half graduate (Oliveros, 2016). We address this problematic reviewing some literature supports to interpret evidence gathered when applying some research instruments such as: pilot survey in two public universities in TEFL programs, a survey for students at risk to drop out and finally an interview and survey applied to the focus group, a group of 30 individuals who dropped out a TEFL program in the last four years. The information gathered using action – research method that attempts to find constant causes to propose solutions to program management along with the faculty. The results we expect to have are related to the research question raised in this work, the pedagogical innovation we propose and our training as a teacher-researcher. First, in relation to the research question, we expect to find the internal factors that are influencing students to take the decision of drop out of a TEFL Program.